2019
DOI: 10.1007/s40572-019-00247-3
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposures Among Hair and Nail Salon Workers: a Scoping Review

Abstract: Purpose of Review To review the literature published from 2014 to 2019 on hair and nail salon workers concerning exposure assessment, reproductive and respiratory endpoints, and endocrine disruption, in relation to workplace exposures. Recent Findings We identified 29 relevant peer-reviewed publications. Overall, there were insufficient studies to determine whether working in these settings is associated with reproductive health endpoints, although prior studies suggest that reproductive effects are of concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…The online version contains supplementary material available at https ://doi.org/10.1007/s0042 0-020-01645 -z. (Quiros-Alcala et al 2019). Quiros-Alcala et al reviewed the literature published from 2014 to 2019 on hair and nail salon workers.…”
Section: Supplementary Informationmentioning
confidence: 99%
See 4 more Smart Citations
“…The online version contains supplementary material available at https ://doi.org/10.1007/s0042 0-020-01645 -z. (Quiros-Alcala et al 2019). Quiros-Alcala et al reviewed the literature published from 2014 to 2019 on hair and nail salon workers.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…They concluded that there is consistent evidence that working in hair and nail salons may increase the risk of respiratory effects. (Quiros-Alcala et al 2019). Potentially hazardous exposures include, but are not limited to, bleaches, conditioners, detergents, dyes, fixatives, and relaxers or straighteners that are most often used as commercially prepared mixtures (Labrèche et al 2003;Pak et al 2013).…”
Section: Supplementary Informationmentioning
confidence: 99%
See 3 more Smart Citations